Educational Tool for Determining Viscosity Coefficient of Cooking Oil Using Arduino UNO - Hilyana, F. Shoufika; Marwoto, Putut; Nugroho, Sunyoto Eko (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2024)
The research aims to determine the quality of cooking oil based on the viscosity coefficient using an Arduino UNO-based viscosity coefficient determining tool. By integrating the Arduino UNO into the viscosity measurement process, this research shows innovation in adapting widely available technology for scientific purposes. The series of tools for determining the value of the viscosity coefficient work if an iron ball enters the fluid and will be detected by magnetic sensors 1 and 2 if it passes through the sensor, which is placed at a predetermined distance. Research was conducted to test the quality of cooking oil by determining the viscosity coefficient. The method research is analyzing recorded videos of the motion of objects falling in oil with Tracker Software. By tracking the video recording of the motion of an object falling in a liquid, data, and graphs of the speed of the falling motion can be obtained. Then from the data obtained, the viscosity value is obtained using the equation. The results of the 5 cooking oils, using the tool, were that oil 1 had a viscosity coefficient of 0.2732 Pa.s; oil 2 with 0.3077 Pa.s; oil 3 with 0.3127 Pa.s; oil 4 with 0.3186; and oil 5 with 0.3218 Pa.s. Meanwhile, the results of the oil viscosity coefficient using manual calculations showed that oil 1 had 0.2733 Pa.s; oil 2 with 0.3089 Pa.s; oil 3 with 0.3136 Pa.s; oil 4 with 0.3188; and oil 5 with 0.3219 Pa.s. The percentage of error that occurs from the tool is 0.17%. The oil with a smaller viscosity coefficient is coconut oil (better quality than palm oil), while the quality of bulk oil is indicated by a larger viscosity coefficient. It could be asserted that the oil's quality improves as the viscosity coefficient decreases.